PARTISIPASI MASYARAKAT DALAM PEMILU SERENTAK TAHUN 2019 DI KABUPATEN BULELENG - GEDE KAMAJAYA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
BSTRACTThe 2019 election is the first simultaneous election in Indonesia. In addition to electing the presidentand vice president, the 2019 election also elects members of the DPR RI, DPD, Provincial DPR, andCity Regency DPRD. The 2019 simultaneous elections were implemented after previously there was alawsuit against Law No. 42 of 2008. One of the most important things in a democratic climate is publicparticipation in the policy-making process and political process. One form of public participation inthe policy-making process and political process is the involvement of citizens in the election process.This study aims to determine the extent of the participation of the Buleleng people in the 2019simultaneous elections. To obtain the results to be achieved as mentioned above, this study uses aqualitative method by collecting data from interviews to document studies. The results of this studyindicate that the number of users of the right to vote in Buleleng Regency is 439,787 people. Inpercentage terms, public participation in simultaneous elections in Buleleng Regency is 73.91%. In the2019 simultaneous elections, there were 596,589 voters in Buleleng. Meanwhile, the number of votingrights users reached 439,787 people who were divided into 2,146 polling stations. The highparticipation rate is due to the success of KPU socialization, massive information in the media. Of allthe regencies in Bali, Buleleng was recorded as one of the districts with a fairly high invalid vote rateof 37,449 while the number of valid votes was 401,818. The high number of invalid votes is due totechnical difficulties, especially for the elderly. In Buleleng Regency itself, the elderly voter rate is thehighest compared to other districts and cities with a total of 92,101 with the number of male voters is42,170 and the number of female voters is 49,931. Keywords: Buleleng Regency, Public Participation, Election, Political Communication